Development of Anchovy Product and the Certification for Community Empowerment in Saramaake Village, East Halmahera, North Moluccas - Faleh Setia Budi; Joko Purnomo; . Sulistiono; . Darmanto; . Arisyono (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2018)
Anchovy (Stolephorus spp) is a main target of lift-net fishery, and it is a main income for the fisherman for long time in Saramaake Village, East Halmahera District. Production in a large number with bulky marketing system and a limited processing activity affect a limited economical value for the community of the village. This community empowerment activities had been done for 6 months, from June–December 2017, aimed to develop the anchovy product and the certification. Methods used in this activity were training and mentoring. Objective targets of the activity were fishermen and fisherman’s wife which are members of Common Business Group and cooperation. Some activities have been done for product development (chili sauce packaged anchovy and labelling) and product certification (certification of halal from the Institute Assessment of Food, Drug and Cosmetics Indonesian Council of Ulama and certification of food of Household Industry from Public Health Service Office in District of East Halmahera). Based on the result of training and mentoring, the object community had gained a knowledge and technology related to the fish processing and certification. Certified marine product have a wider market and marketable in some shops in Ternate and Buli.